ANALYSIS LEARNING SOCIAL SCIENCE CHARGED THE VALUES OF ENTREPRENEURSHIP IN PRIMARY SCHOOL (Case Study in Social Science Education in Class IV SDPN Pajagalan 58 Bandung) - Dadang Iskandar; Lutma Ranta Allolinggi; Acep Roni Hamdani (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2016)
Abstract. Entrepreneurship education is a government program that is conducted every level of education. Implementation of the values of entrepreneurship learning in primary schools is an effort to promote entrepreneurship, so that people can develop into a reliable personal and be the generation that can create jobs. This study aims to assess the extent to which the learning of Social Sciences can provide space in growing the value of entrepreneurship in primary school students. This research was conducted in SDPN Pajagalan 58 with qualitative approach case study method. The subject is the person responsible for entrepreneurship education program, one teacher of Social Sciences and seventeen students of class IV. Based on the survey results revealed that entrepreneurship education program has been designed as possible into school programs that are implemented on an ongoing basis. The values of entrepreneurship has been published in school activities such as extracurricular activities, events and activities programmed habituation. Planning learning Social Sciences laden entrepreneurial values starting from the manufacture of the syllabus and lesson plans. Implementation of classroom learning is done in accordance with the lesson plan gives more space for students to develop a personality. Assessment of learning laden entrepreneurial values is done through observation and checks on student attendance. At the time of the learning takes place, the student has demonstrated an attitude / entrepreneurial character that is honest, self-discipline, confidence, leadership, creative, independent, hard work, responsibility, curiosity, communicative, and cooperation. The main problem is the plan that is prepared teacher is not maximized and not yet fully apply in learning. From the results of this study are expected to provide benefits for the development of entrepreneurship education in primary schools, especially in SDPN Pajagalan 58 and become material for the evaluation of Bandung City Education Department.